Beyond HER2: Targeting the ErbB receptor family in breast cancer. (September 2022) - Drago, Joshua Z.; Ferraro, Emanuela; Abuhadra, Nour; Modi, Shanu
Highlights: Prior efforts to target the ErbB receptor family beyond HER2 have been inadequate. Novel therapeutic approaches such as antibody-drug conjugates hold promise. Better patient selection can improve the potential of these agents in breast cancer. Abstract: Targeting the HER2 oncogene represents one of the greatest advances in the treatment of breast cancer. HER2 is one member of the ERBB-receptor family, which includes EGFR (HER1), HER3 and HER4. In the presence or absence of underling genomic aberrations such as mutations or amplification events, intricate interactions between these proteins on the cell membrane lead to downstream signaling that encourages cancer growth and proliferation. In this Review, we contextualize efforts to pharmacologically target the ErbB receptor family beyond HER2, with a focus on EGFR and HER3. Preclinical and clinical efforts are synthesized. We discuss successes and failures of this approach to date, summarize lessons learned, and propose a way forward that invokes new therapeutic modalities such as antibody drug conjugates (ADCs), combination strategies, and patient selection through rational biomarkers.